Effect of sodium bicarbonate as blowing agent on production of epoxy shape memory foam using aqueous processing method - Muhammad Syazwan Fauzi; Du N.U. Lan; Hakimah Osman; Supri A. Ghani (Universiti Kebangsaan Malaysia, 2015)
Epoxy shape memory foam (ESM) was produced by an advanced aqueous method. Mixture of epoxy, sodium bicarbonate, hardener and ammonium chloride was premixed and emulsified in distilled water by using high speed stirring (at 1200 rpm). The content of sodium bicarbonate used was 5, 10, 15 and 20 phr. Besides that, ammonium chloride was used (based on stoichiometrical content) to also function as acidifying agent in initiating the decomposition process of sodium bicarbonate at lower foaming temperature. The foam morphology was observed using SEM. It was found that higher sodium bicarbonate produced more porosity, more cell size, thinner cell wall and more cell interconnection. Epoxy shape memory foam with 10 phr of sodium bicarbonate exhibited good shape memory property and better compression set. Shape memory behaviour was measured by the recovered time of the transformed sample to its original shape.